The relationship between family climate and identity development processes: the moderating role of developmental stages and outcomes - Prioste, A.; Tavares, P.; Silva, C. S.; Magalhães, E. (Journal of Child and Family Studies, 2020)
Objectives This study aimed to analyze the relationship between family climate and identity development, and the moderating role of the development stage and (in)adaptive outcomes in that relationship. Methods A cross-sectional quantitative study was developed with 387 participants (65.4% female; 162 adolescents aged between 15–19 years and 225 emerging adults aged between 20–25 years). Data was collected using self-reported measures: Sociodemographic questionnaire, Dimensions of Identity Development Scale, Brief Symptom Inventory and Family Climate Inventory. Results The results of structural equation modeling showed moderating effects of developmental stage (??2 (38) = 93.47, p = 0.009) and outcomes (??2 (38) = 63.50, p = 0.006) in the relationship between family climate and identity development, suggesting that family cohesion predicted identity outcomes differently for adolescents and emerging adults, as well as for participants with adaptive and non-adaptive developmental trajectories. Also, family conflict predicted identity formation outcomes differently in function of developmental outcomes. Conclusions As high levels of family conflict and cohesion are associated to higher levels of exploration in depth, future studies should focus on enmeshed family interactional patterns and its outcomes on children across development. Our data highlights the role of family climate on the identity development in adolescence and emerging adulthood and the importance of analyzing family risk and protection factors as conditions for individual developmental outcomes.